The effect of mother tongue-based multilingual education on the Science achievement and metacognitive learning orientations of Ilocano grade 3 pupils: Implications for policy and practice - Jerome G. Santiago (Universiti Pendidikan Sultan Idris, 2021)
The implementation of Mother Tongue-Based Multilingual Education (MTB-MLE) in the Philippines is being criticized by stakeholders whether it is a better approach for pupils in the primary levels than the monolingual-Second language (MSL) approach using Tagalog. Several studies in the past decade attempted to test the effect of MTB-MLE on pupils' learning on different subject areas. However, there is yet no available study on the effect of MTB-MLE on Science learning variables such as metacognitive learning orientations and achievement among Grade 3 learners whose mother tongue is Ilocano. This quasi-experimental study was conducted to test the effect of MTB-MLE on the academic achievement, metacognition, learning processes, and self-efficacy of Ilocano Grade 3 pupils in Science learning. Fifteen (15) Ilocano pupils were randomly selected from each of two elementary schools of a district in Isabela Province, Philippines. The two groups were taught in Science using Tagalog-only (MSL) and Ilocano-Tagalog (MTB-MLE), respectively. Pre and post-assessment were conducted to gauge the pupils’ traits in Science. Descriptive statistics, independent-samples t-test, analysis of covariance, and paired samples t-test were used to analyze the data. There was no significant difference between the achievement, metacognition, self-efficacy, and learning processes of the MTB-MLE and the MSL pupils in Science. Moreover, the learning processes of the MSL pupils such as monitoring-evaluating-planning, learning risk awareness, and control of concentration did not significantly improve. Therefore, this study recommends the implementation of MTB-MLE in the primary level, and provides implications for policy and practice for better learning outcomes.